An integrated geospatial correlation analysis and human health risk assessment approach for investigating abandoned industrial sites. (1st September 2021) - Hu, Guangji; Liu, Huan; Chen, Chang; Li, Jianbing; Hou, Haobo; Hewage, Kasun; Sadiq, Rehan
Abstract: An integrated geospatial correlation analysis (GCA)-human health risk assessment (HHRA) approach was developed to investigate abandoned industrial sites featured by heterogeneous contamination data. Critical areas of high health risk concerns can be prioritized for remediation using the integrated approach. An abandoned chemical complex site in Hubei, China was investigated as a case study. GCA and HHRA were performed using soil and groundwater sampling data collected in 2016 and 2019. Benzene, chlorobenzene, dichlorobenzenes, 2-nitrochlorobenzene, and α-hexachlorocyclohexane were determined to be critical contaminants in soil. The 2019 sampling data revealed new contaminated locations that were not found in the 2016 sampling campaign. High concentrations (89.81–386.55 mg/L) of vinyl chloride were also found in groundwater samples. Several critical location clusters of high concentrations of dichlorobenzenes, chlorobenzene, and α-hexachlorocyclohexane were found within the site according to the GCA outcomes. These contaminants could pose significant cancer and non-cancer risks to onsite workers. The critical areas were ranked according to cancer and non-cancer risks estimated by HHRA, respectively, for informed remediation planning. Among the critical contaminants, α-hexachlorocyclohexane, 2-nitrochlorobenzene, and 1, 4-dichlorobenzene in soil, as well as vinyl chloride in groundwater, contributed a predominant part to the total health risk. The integrated approach can be used to assess the contamination of other similar abandoned industrial complex sites. Graphical abstract: Image 1 Highlights: An integrated geospatial correlation and health risk analysis approach was proposed. The approach can help assess contamination of sites with heterogeneous data. Geospatial correlation analysis identifies critical areas with severe contamination. Critical areas are prioritized according to human health risk assessment results.